2003
DOI: 10.4049/jimmunol.170.5.2409
|View full text |Cite
|
Sign up to set email alerts
|

The 19-kDa Mycobacterium tuberculosis Protein Induces Macrophage Apoptosis Through Toll-Like Receptor-2

Abstract: Macrophages infected with Mycobacterium tuberculosis undergo increased rates of apoptosis. Important objectives are to define the microbial factors that cause apoptosis, the mechanisms involved and the impact on infection. The 19-kDa M. tuberculosis glycolipoprotein (p19) is both cell wall-associated and secreted and is a candidate virulence factor. We investigated the potential of recombinant, His-tagged p19 lacking the secretion/acylation signal to induce macrophage apoptosis. The TUNEL assay and annexin V b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
163
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(184 citation statements)
references
References 44 publications
14
163
2
2
Order By: Relevance
“…Our results showed that rMPT83 induced the expression of mRNA and protein for TNF-a, IL-6, and IL-12 p40, and these effects were attenuated or blocked by anti-TLR2, indicating that the effects of rMPT83 on cytokine production are mediated by TLR2. The production of cytokines was lost when rMPT83 was digested with proteinase K, similar to the effects observed with two other mycobacterial lipoglycoproteins, p19 and 38-kDa Ag (9,10). Furthermore, the production of cytokines, particularly TNF-a, was higher in macrophages from wild-type mice than in macrophages from TLR2 2/2 mice.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results showed that rMPT83 induced the expression of mRNA and protein for TNF-a, IL-6, and IL-12 p40, and these effects were attenuated or blocked by anti-TLR2, indicating that the effects of rMPT83 on cytokine production are mediated by TLR2. The production of cytokines was lost when rMPT83 was digested with proteinase K, similar to the effects observed with two other mycobacterial lipoglycoproteins, p19 and 38-kDa Ag (9,10). Furthermore, the production of cytokines, particularly TNF-a, was higher in macrophages from wild-type mice than in macrophages from TLR2 2/2 mice.…”
Section: Discussionsupporting
confidence: 51%
“…TLR2 mediates cellular responses to diverse molecular structures. In the context of M. tuberculosis infection, the recognition of M. tuberculosis cell wall components by TLR2 results in the production of proinflammatory molecules (7)(8)(9), the induction of apoptosis (10), and the formation of macrophage giant cells (11); these effects contribute to both host protection and immunopathology. Polymorphisms in the human TLR2 gene are associated with enhanced susceptibility to leprosy and tuberculosis (12)(13)(14).…”
mentioning
confidence: 99%
“…Our finding that the lspA-/-mutant did not provoke apoptosis supports the view that mature lipoproteins are necessary for induction of apoptosis also in PMNs, as has previously been described in macrophages using recombinant 19kD lipoprotein [41]. This is further supported by complementation of the lspA-/-mutant with triacylated Pam 3 CysSK 4 , mimicking ligands such as 19kD, which restored the apoptosis-inducing capacity.…”
Section: Figure 7 Mtb-induced Apoptosis In Pmns Is Not Due To Permeabsupporting
confidence: 90%
“…The transient overexpression and activation of TLR2 mediated apoptosis in HEK293 cells, although to a lesser extent as compared with TLR4. Previous studies, that were reporting apoptosis through TLR2 stimulation, were conducted predominantly on human monocytic THP-1 cells, THP-1-derived macrophages, and human Schwann cells (12,47,60,61), while our experiments were done on mouse J774A.1 and primary peritoneal macrophages. This suggests that there may exist cell type-specific differences in TLR-responsive apoptosis signaling, which could be related to the distinct engagement of intracellular adapter proteins by TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 99%